The Effect of Diabetes Self-Management Education (DSME) on Self-Efficacy of Type 2 Diabetes Mellitus Patients at the Kassi-Kassi Public Health Center - Darwis, Nurhaliza; Zulkifli, Andi; Amiruddin, Ridwan (International Journal of Statistics in Medical Research, 2026)
Type 2 diabetes mellitus requires continuous self-management, yet many patients have limited confidence in performing daily care. This study evaluated the effect of Diabetes Self-Management Education (DSME) on self-efficacy among patients with type 2 diabetes mellitus at the Kassi-Kassi Community Health Center, Makassar. A non-randomized quasi-experimental pretest–posttest design with a control group was used. A total of 120 patients were recruited consecutively and divided into an intervention group (n=60) and a control group (n=60). The intervention group received four structured 60-minute face-to-face DSME sessions over two weeks, supported by modules, booklets, and educational videos, whereas the control group received usual care and an educational booklet. Self-efficacy was measured using the 20-item Diabetes Management Self-Efficacy Scale. Data were analyzed using paired and independent t-tests and Difference-in-Differences analysis. Mean self-efficacy increased from 38.43±6.54 to 90.90±5.87 in the intervention group and from 39.55±6.26 to 80.53±6.39 in the control group. The posttest mean difference was 10.37 points (95% CI: 8.15–12.59; p<0.001; Cohen’s d=1.69). The Difference-in-Differences estimate was 11.49 points. Structured DSME was associated with a substantial short-term improvement in self-efficacy and may be considered for integration into routine primary diabetes care. Further multicenter randomized studies with longer follow-up and clinical outcomes are still needed.